Nanotechnology: A Valuable Strategy to Improve Bacteriocin Formulations - Fahim, Hazem A.; Khairalla, Ahmed S.; El-Gendy, Ahmed O. (Frontiers in Microbiology, 2016)
Bacteriocins are proteinaceous antibacterial compounds, produced by diverse bacteria, which have been successfully used as: (i) food biopreservative; (ii) anti biofilm agents; and (iii) additives or alternatives to the currently existing antibiotics, to minimize the risk of emergence of resistant strains. However, there are several limitations that challenge the use of bacteriocins as biopreservatives / antibacterial agents. One of the most promising avenues to overcome these limitations is the use of nanoformulations. This review highlights the practical difficulties with using bacteriocins to control pathogenic microorganisms, and provides an overview on the role of nanotechnology in improving the antimicrobial activity and the physicochemical properties of these peptides.